Brain Neuroplasticity Effects on the Occurrence of Anterior Cruciate Ligament Injury and the Effect of this Injury on Brain Function and Structure: A Systematic Review - Hassan Daneshmandi; Mostafa Payandeh; Zaher Mohammad Ashour (University of Social Welfare and Rehabilitation Sciences, 2022)
Objective: The present study aimed to investigate the effect of brain neuroplasticity on the incidence of anterior cruciate ligament (ACL) injury and on brain function and structure before and after ligament reconstruction and after a period of rehabilitation exercises. Materials & Methods: In this review study, a search was conducted in PubMed, Scopus, Web of Science, Google Scholar, ScienceDirect, MedLine, Pedro, CINAHL, SPORTDiscus, and Cochrane Databases as well as national databases on related studies published from 1970 to 2021 using keywords in Persian and English related to the research topic. Results: The initial search yielded 65 articles. Based on the inclusion and exclusion criteria, 24 articles were selected for review of which 5 articles prospectively examined the effect of brain neuroplasticity on the incidence of ACL injury. Their results showed that the brains of people with ACL injury was different from the uninjured people, especially in the motor-sensory part of the cerebral cortex and cerebellum, which caused errors during movement planning of these persons. Ten articles examined the effect of ACL injury before reconstruction on brain function and structure and reported that changes occur in the level of motor-sensory cortex of the brain at least two weeks after the injury; after one year, these structural and functional changes were widely increased in injured people compared to healthy people. These studies also showed that the ligament dysfunction and the damage to mechanical receptors cause the reorganization of the central nervous system. In injured people, the control activity of motor-visual areas and their need for visual feedback have increased. Seven articles examined these changes after ligament reconstruction and showed that the brain neuroplasticity or functional and structural changes resulting from the injury not only did not return to normal conditions, but also increased after a while despite the reconstruction. Two articles examined these changes after a period of rehabilitation exercises and showed that functional and  Conclusion: The changes in the brain after ACL injury not only persist after ligament reconstruction, but also increase after reconstruction. The common rehabilitation exercises whose main focus is not on eliminating these functional and structural changes in the brain cannot overdrive this negative neuroplasticity after injury which is one of the important causes of secondary injury and subsequent complications. In developing exercises to prevent ACL injury and for rehabilitation, it is better to use the new principles of motor learning and exercises related to visual feedback along with conventional exercises to overdrive negative neuroplasticity created in the brain and create positive neuroplasticity to support ACL.